Experimental Two‐Way Communication with One Photon. Issue 11 (18th September 2019) - Massa, Francesco; Moqanaki, Amir; Baumeler, Ämin; Del Santo, Flavio; Kettlewell, Joshua A.; Dakić, Borivoje; Walther, Philip
Abstract: Superposition of two or more states is one of the most fundamental concepts of quantum mechanics and provides a basis for several advantages offered by quantum information processing. This work reports the experimental demonstration of two‐way communication between two distant parties that can exchange only a single particle once, an impossible task in classical physics. This is achieved through preparation of a single photon in a coherent superposition of the two parties' locations. Furthermore, it is shown that this concept allows the parties to perform secure and anonymous quantum communication employing one particle per transmitted bit. These important features can lead to the realization of new quantum communication schemes, which are simultaneously anonymous, secure, and resource‐efficient. Abstract : The present work demonstrates two‐way signaling between two distant parties via the one‐way exchange of a single photon in superposition. Furthermore, this concept is used to implement a novel secure quantum communication protocol, which allows the parties to hide the direction of communication. These results show the power of quantum superposition as a resource for communication.